Influence of pulsed plasma treatment on phase composition and hardness of Cr3C2-NiCr coatings - D.N. Kakimzhanov; B.K. Rakhadilov; Yu.N. Tyurin; O.V. Kolisnichenko; L.G. Zhurerova; M.K. Dautbekov (Eurasian Journal of Physics and Functional Materials, 2021)
In this study, the research results of the influence of pulsed plasma treatment on phase composition, hardness, and roughness of Cr3C2 -NiCr coatings are presented. The Cr3C2 -NiCr coating was applied to substrate 12Kh18N10T stainless steel by detonation spraying method. To change the physical and mechanical properties of sprayed coating’s surface layers, subsequent pulse-plasma treatment was used. The pulse-plasma treatment leads to changing the roughness of Cr3C2 -NiCr coating. The results of mechanical tests showed that after pulsed plasma treatment, the hardness of Cr3C2 -NiCr coating is increased. Based on X-ray diffraction analysis, it was found that the hardness increasing of coating is associated with phase transformations on the surface layer, in particular, the formation of the oxide phase and an increase in the number of carbide particles.